2004
DOI: 10.1103/physrevb.69.085324
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport calculations for self-assembled monolayers of 1,4-phenylene diisocyanide on Au(111) contacts

Abstract: We report on electronic transport calculations for self-assembled mono-layers (SAM) of 1,4phenylene diisocyanide on Au(111) contacts. Experimentally one observes more structure (i.e peaks) within the measured conductance curve for this molecule with two cyanide end-groups, compared to measurements with molecules having thiol end-groups. The calculations are performed on the semi-empiric extended Hückel level using elastic scattering quantum chemistry (ESQC) and we investigate three possible explanations for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…For both geometries, and irrespective of the employed method, the low-bias transport is dominated by the LUMO. This is in qualitative agreement with previous results [58,59]. The DFT conductance values in these two examples are 4.8 × 10 −2 G 0 (TT1) and 0.14G 0 (TT2).…”
Section: Heat Dissipation In Benzene-based Single-molecule Junctionssupporting
confidence: 93%
“…For both geometries, and irrespective of the employed method, the low-bias transport is dominated by the LUMO. This is in qualitative agreement with previous results [58,59]. The DFT conductance values in these two examples are 4.8 × 10 −2 G 0 (TT1) and 0.14G 0 (TT2).…”
Section: Heat Dissipation In Benzene-based Single-molecule Junctionssupporting
confidence: 93%
“…In addition, intermolecular interactions that also lead to conductance fluctuations are completely eliminated in the covered molecule because the intermolecular distance necessarily becomes large owing to the presence of the α‐CD molecule; an intermolecular distance of ≈15 Å was observed in X‐ray diffraction measurements. The influence of neighboring molecules at an intermolecular distance of 15 Å on the conductance is negligibly small 29. Therefore, we conclude that protection of a single‐molecule wire by using a covering molecule such as α‐CD is quite effective for the suppression of structural and hence conductance fluctuations in single‐molecule junctions.…”
Section: Resultsmentioning
confidence: 76%
“…We showed that the conductance of the π-stacked system decreased with the number of π molecules, and the decrease in conductance per unit of electron-transport distance was comparable to that of the conventional single-molecule junction. Dahlke et al investigated the effect of the surrounding molecules on the single phenylene diisocyanide molecule junction, by means of theoretical calculations [ 9 ]. The electronic structure and conductance of the phenylene diisocyanide molecule were affected by surrounding phenylene diisocyanide molecules when the distance between the molecules was less than 0.6 nm.…”
Section: Introductionmentioning
confidence: 99%